Spectral radiative analysis of bio-inspired H2 production in a benchmark photoreactor: A first investigation using spatial photonic balance. (26th April 2018) - Supplis, Caroline; Gros, Fabrice; Dahi, Ghiles; Dauchet, Jérémi; Roudet, Matthieu; Gloaguen, Frederic; Cornet, Jean-François
Abstract: The iron–thiolate complex [Fe2 (μ-bdt)CO6 ] (bdt = 1, 2-benzenedithiolate) is a simplified model of the active site of diiron hydrogenase enzymes. Here, we describe the implementation of this noble-metal-free catalyst in aqueous solutions using eosin Y as photosensitizer and triethylamine as an electron donor in an experimental bench specially designed for the study of H2 photoproduction. The bench is composed of an adjustable visible light source, a fully equipped flat torus photoreactor and analytical devices. Rates of H2 production under varied experimental conditions were obtained from an accurate measurement of pressure increase. A spectral radiative analysis involving blue photons of the source primarily absorbed has been carried out. Results have proven the rate of H2 production is proportional to the mean volumetric rate of radiant light absorbed demonstrating a linear thermokinetic coupling. The bio-inspired catalyst has proven non-limiting and reveals interesting capabilities for future large scale H2 production. Graphical abstract: Highlights: A bioinspired photocatalytic system producing H2 in a photoreactor was evaluated. A spectral radiative analysis of the system was carried out. Evidence was obtained that linear kinetic coupling with light absorption rate occurs. The bio-inspired catalyst reveals strong capabilities from an engineering analysis.